Validity and Actuality of Marín’s Thought 70 Years After the Foundation of CAEN - Merino Amand, Marco Antonio (2020)
The National Center for Higher Studies (CAEN) was founded based on the critical thinking of Major General José del Carmen Marín, who pointed out that the dogmatic ideas and concepts that serve as the basis of a State’s public policies must be interpreted according to the national reality, in order to provide welfare to society; for this reason, the research carried out focused on the validity and currency of Marin’s thinking 70 years after the foundation of CAEN. The research was of a historical-descriptive type, with a qualitative approach and a non-experimental design, and the population was made up of the historical bibliographic material in which Marín’s thought was expressed, the selected sample being the articles and documents found in the university libraries. From Peru. The results found showed that Marín thought was forged based on the General’s experiences, which generated turning points that allowed him to change the interpretation of the concepts used literally, to a situational interpretation, allowing him to promote measures that guarantee the citizen welfare in relation to national security and defense. It was concluded that the National Agreement, approved on April 29, 2019, called Vision of Peru by 2050, reflects the validity and currency of Marin’s thinking, since it focuses on the decisions made at a given time does not affect the well-being of future generations, which is related to the critical thinking enunciated by Marín 70 years ago.